COP29 at the climate crossroads: achievements, gaps, and implications for a warming world - Khan, M. Imran; Asfand, Faisal; Asif, Muhammad; Hadi, Noor Ul; Farooq, Muhammad; Kurniawan, Tonni Agustiono; Al-Ghamdi, Sami G. (Frontiers in Climate, 2026)
The 29th Conference of the Parties (COP29), held in Baku, Azerbaijan, in 2024, convened amidst escalating climate crises and unprecedented global warming, with 2024 recorded as the hottest year in history. This perspective critically examines the outcomes of COP29, evaluating its achievements, gaps, and implications for global climate governance. Notable achievements include the establishment of the New Collective Quantified Goal (NCQG), tripling climate finance commitments to $300 billion annually by 2035, and the operationalization of Article 6 carbon markets, which promise to mobilize significant resources for mitigation and adaptation efforts. Progress was also made on the Loss and Damage Fund, addressing climate justice for vulnerable nations, and the launch of the Baku Adaptation Roadmap, a structured pathway for advancing global resilience. These initiatives promise enhanced transparency, increased climate finance, and a structured approach to adaptation. However, the summit fell short of delivering transformative actions necessary to align with the 1.5°C target, particularly in areas such as fossil fuel phaseout, equitable finance mechanisms, and loss and damage support. The NCQG's reliance on private finance and loans, rather than grants, underscored ongoing inequities, while insufficient funding and delayed implementation of the Loss and Damage Fund further strained trust between developed and developing nations. Geopolitical tensions, coupled with the influence of fossil fuel interests, diluted negotiations, leaving critical issues deferred to COP30. The findings emphasize the need for robust accountability, equitable financial mechanisms, and inclusive frameworks to align global efforts with the escalating urgency of the climate crisis. As the world turns to COP30 in Belém, Brazil, this perspective provides actionable insights into the transformative changes required to achieve a sustainable and equitable future.